Deconstructing Hollywood War Cinema: The Construction of the Enemy in Inglorious Basterds as Postmodern Enemy - Sauci, Kholifatul (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
This research examines the construction of the enemy in Quentin Tarantino's Inglourious Basterds (2009) as postmodern enemy through the portrayal of the Nazi. Applying Derrida's deconstruction theory to see how Hollywood cinematic convention is being deconstructed, the analysis shows that the Nazi are being deconstructed through the following construction: 1) wearing distinctive outfit, 2) being dehumanized as evil, 3) having different purpose from the hero, 4) being on the losing side, and 5) being racially different. The Nazi shows some qualities of not being stereotypical enemy: they are depicted to show patriotism, loyalty, and compassion. The blurry characteristics between hero and enemy shows postmodernity.